Implementation of Kipin school 4.0-Based Learning Model in increasing Learning Motivation at SDI NU Lawang - Abdul Malik Karim Amrullah; Lukman Sholeh; Muhammad Fajar Fatihatur Rizki; Shabrina Ratu Alam Shufiatuddin (Ma'arif Journal of Education, Madrasah Innovation and Aswaja Studies, 2023)
The focus of this research is on the Implementation of the Kipin School 4.0 Based Learning Model in Increasing Learning Motivation. This research is a descriptive qualitative research with a case study approach. The aim of this research is to be able to fully and thoroughly describe the Kipin School 4.0-Based Learning Model in Increasing Learning Motivation. Data collection techniques used in this study were observation, interviews, and documentation studies. Research informants namely school principals, curriculum department, teachers, and five students as respondents. Data analysis techniques using data analysis Miles and Hubbeman consist of reducing data, presenting data, and drawing conclusions. The results of this study concluded that the Kipin School 4.0-Based Learning Model is very helpful in the learning process in this 4.0 era so that teachers can more easily convey material that is already in the Kipin school 4.0 application.